The ethics of information technology and business - De George, Richard T. (Malden, MA : Blackwell Pub., 2003)
The book explores a wide range of topics, including marketing, privacy, and the protection of personal information; employees and communication privacy; intellectual property issues; the ethical issues of e-business; internet-business ethics problems; and the ethical dimension of information technology on society.
Ethics and the information revolution -- Marketing, privacy, and the protection of personal information -- Employees and communication privacy -- New, intellectual, and other property -- Ethical issues in information technology business and e-business -- Ethical issues on the Internet -- Information technology and society: business, the digital divide, and the changing nature of work.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Business ethics; Information technology -- Moral and ethical aspects; Morale des affaires; Technologie de l'information -- Aspect moral; BUSINESS & ECONOMICS -- Business Ethics; Business ethics; Information technology -- Moral and ethical aspects; Electronic Commerce; Neue Medien; Online-Informationssystem; Unternehmensethik; Bedrijfsethiek; ICT; Technologies de l'information.; Morale des affaires